Master tracks in different resolutions during POLAR 6 campaign ANT_GEA_2016_2017 - Graeme Eagles (PANGAEA, 2018)
This dataset was created via processing of raw position data acquired by the GPS sensor for scientific equipment on Polar 6/Polar 5 to receive a validated master track which is used as reference of further expedition data.